HIERARKI ORGANISASI & TRANSMISI PENGETAHUAN HASIL PRODUKSI PERTUNJUKAN PADA MANAJEMEN YOGYAKARTA ROYAL ORCHESTRA (STUDI KASUS: PERTUNJUKAN RARÉ RUMPAKA YOGYAKARTA ROYAL ORCHESTRA) - Setianjaya, Iwan; Dyah Fitriasari, Rr. Paramitha; Mulyana, Aton Rustandi (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2023)
This research aims to reassemble the presence of hierarchical sketches in the work scheme that applies in the performance management of the Yogyakarta Royal Orchestra through a case study of the Raré Rumpaka 2023 performance. The study of performance management at the Yogyakarta Royal Orchestra is researched through the approach of management and bureaucracy. The effort was made to see the depth of the relationship that can be found between the orchestra’s performance governance and the royal bureaucracy. Another research focus is to see the extent to which knowledge transmission can be found from the journey of performance activities consisting of the preparation process, implementation to closing. This research uses a descriptive qualitative method to look at the phenomena of problems and events that occur in the research arena. The data was collected through interpersonal interview procedures with resource persons with research schemes including observation, field notes and processing of field documentation results. The data analysis process is carried out based on four stages, namely data collection, data reduction, data presentation and conclusion making. The results of the research attempt to reveal the openness of information in the implementation of the Raré Rumpaka performance, which focuses on the managerial management system of the Yogyakarta Royal Orchestra consisting of the existence of the royal bureaucratic system, the hierarchical work scheme that applies, and the results of knowledge transmission generated after the performance.